Our experience of 200 cases of thyroid surgery under local anaesthesia versus general anaesthesia - Chintale, Sambhaji G.; Kirdak, Vilas R.; Jatale, Sonali P.; Shaikh, Kaleem (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Local Anaesthesia is now being accepted universally as a safe alternative to general anaesthesia for thyroid surgery. This study was carried out to compare the outcomes of patients undergoing thyroid surgery under local and general anaesthesia. Methods: 200 patients who underwent thyroid surgery for benign and malignant diseases under local and general anaesthesia from March 2014 to march 2017 were analysed. Patient characteristics analysed were age, sex, pathology lesion size, operating time, length of stay, cost and post-operative complications. Results: Mean lesion sizes were 4.5 cms and 6.5 cms in local and general anaesthesia group respectively. Mean operating time was 50, 5 minutes and 75.5 minutes in local anaesthesia and general anaesthesia group respectively. Mean cost incurred was Rs. 2500 in local anaesthesia and Rs. 5500 in general anaesthesia group. Mean length of hospital stay was 40, 25 hours and 75.06 hours in local anaesthesia and general anaesthesia group respectively. Conclusions: Local anaesthesia is a safe alternative to general anaesthesia for patients undergoing thyroid surgery. Use of local anaesthesiahas resulted in a decreased length of stay, cost and means operating time, hence useful in a setup with limited anaesthesia time and increased work load.